Pomegranate (Punica granatum L.) gel extract as an antioxidant on the shear bond strength of a resin composite post-bleaching application with 40% hydrogen peroxide - Indes Rosmalisa Suratno; Irfan Dwiandhono; Ryana Budi Purnama (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Tooth discoloration can be treated with tooth bleaching. Bleaching using 40% hydrogen peroxide can reduce the shear bond strength of resin composite because there are free radicals on the tooth surface, so it can delay the restoration. The application of antioxidants can eliminate free radicals after the bleaching procedure and increase the shear bond strength of the composite resin. The common antioxidants are ascorbic acid and natural ingredients, such as pomegranate (Punica granatum L.). Purpose: To determine the effect of pomegranate extract gel on the shear bond strength of composite resin after 40% hydrogen peroxide bleaching application. Methods: This research used 32 maxillary first premolars that were divided into four groups. The samples were bleached, then the labial was prepared and antioxidant gel was applied: group P1 pomegranate gel extract of 5%, group P2 pomegranate gel extract of 10%, group K1 positive control ascorbic acid gel of 10% and group K2 as the negative control. The samples were restored with a nanohybrid composite resin. The shear bond strength was tested using a universal testing machine. The data were tested using a one-way ANOVA followed by a post-hoc LSD test. Results: The pomegranate gel extract increased the shear bond strength of the composite resin after the bleaching procedure of 40% hydrogen peroxide compared with the ascorbic acid gel group and the negative control group. The one-way ANOVA test showed a significant difference (p<0.05). The post-hoc LSD test showed significant differences between the treatment and negative control groups (p<0.05). Conclusion: The pomegranate gel extract as an antioxidant increased the shear bond strength of the composite resin restoration after the 40% hydrogen peroxide bleaching application.